Pengelolaan Program Qurani Leadership SD X Bandung - Eka Saniah; Eko Surbiantoro (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. This research is motivated by the importance of education that not only facilitates in the field of science and technology but also accompanied by character or moral education. Such education can be realized by schools that have programs that facilitate both by instilling Islamic values in every learning. In addition, in order for its implementation to run purposefully and regularly, it takes a program management to achieve an educational goal. The management starts from planning activities, implementation to evaluation. Based on this background, the formulation of the problem in this study is